Aplicaciones pedagógicas del Penetrómetro GY-3 en procesos de transformación Agroindustrial. - Mera Franco, Evelyn Samanta (2022)
The objective of this study was to carry out a manual of pedagogical applications of the GY-3 Penetrometer in Agro-industrial transformation processes, with the purpose of incorporating the GY-3 Penetrometer to the laboratories of the Agro-industrial Engineering Career, it is a measurer of fruits and vegetables. The functions of the parts of the instrument are essential to perform the respective measurements. The characteristics of this instrument determine the degree of ripeness in which the fruit is for its due processing. The technical requirements of the instrument, the parts and their functions were determined, after which a description of the procedure was made. The different types of routine, preventive and corrective maintenance that must be performed on the instrument to prevent its malfunction were presented. Finally, practices of pedagogical applications were carried out in the laboratory using the instrument where the texture conditions of the peach were determined with the piston of 8 mm of 3.5 kg / cm² and of the piston 11 mm of 7.5 kg / cm², the Claudia with the piston of 8 mm of 3.5 kg/ cm² and of the 11 mm piston of 4.5 kg/ cm², and the kidney tomato with the 8 mm piston of 2.2 kg/ cm² and of the 11 mm piston of 4.6 kg/ cm² on different days of storage , obtaining the best values of its texture of the fruits for its processing, for which there were guide sheets that contained each of the parameters that had to be carried out at the time of the practice and as results it was reflected in reports according to the data obtained from the measurement of the hardness of fruits and vegetables. In addition, a matrix is attached in which the subjects that will use the instrument are detailed.